Simulations for resource-allocation protocol optimization for MIL-STD-188-186 over a UHF SATCOM network - Chandler, Edward William (Array, 2019)
A simple simulation tool was previously developed to simulate the operation and performance of demand-assigned communication networks having time-varying data traffic patterns. Such networks use protocols to increase or decrease the resources allocated to a network node as the resource needs at that node change. These resource-allocation protocols have parameters such as numerical thresholds for requesting or releasing resources. The additional simulator development and execution described herein allows a comparison of performance metrics that result when using the existing MIL-STD-188-186 protocol versus using a proposed alternative protocol. The network behavior revealed by the simulation results also allows examining network performance trade-offs as values for the protocol parameters are adjusted. Although commercially available simulation tools could be used for these simulations, such tools are often expensive and sometimes complicated to adapt to new and not yet standardized protocols. The simple simulation tool that was previously developed is described in an earlier paper and is programmed as an Excel spreadsheet. It has now been adapted to allow comparing an existing resource-allocation protocol versus a proposed protocol for MIL-STD-188-186. The simulator allows examination of performance metrics such as the average number of assigned time slots per frame assigned to a transmitting node that has a specified message generation rate, the percentage of generated messages that are discarded prior to transmission due to being queued for an excessive time, and a histogram showing the percentage of messages transmitted with each possible message delivery time.